PEMBELAJARAN MENDALAM SEBAGAI PROSES EKSISTENSIAL DALAM MEWUJUDKAN KEOTENTIKAN DAN REFLEKSI DIRI PESERTA DIDIK - Yulisia Rezky Kirana; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article analyzes deep learning as an existential process that positions students as free, conscious, and reflective individuals within the learning experience. Through a literature review of core existential concepts and humanistic educational approaches, the study highlights that deep learning goes beyond conceptual understanding toward meaning-making, identity formation, and the development of personal authenticity. These principles align with Indonesia’s Merdeka Belajar curriculum, which emphasizes learner autonomy, independence, and holistic development. Deep learning enables students to connect knowledge with personal experiences, making the learning process more meaningful and relevant to their lives. Teachers serve as existential facilitators who create dialogic, reflective, and humanistic learning environments where knowledge is offered as lived experience rather than imposed content. The findings indicate that integrating existential perspectives with deep learning contributes to a humanizing educational ecosystem that fosters self-awareness, personal responsibility, and reflective capability in students. Thus, education functions not merely as the transmission of knowledge but as a transformative process that guides learners toward becoming authentic individuals who are aware of their existence and the meaning behind their learning experiences. Keywords: Deep learning, Existentialism, Authenticity, Self-reflection, Humanistic Education